Laboratory scale eggshell membrane separation and hydrolysis / Nurul Syazwina Nor Hisamuddin ... [et al.] - Nor Hisamuddin, Nurul Syazwina; Abdul Muttalib, Siti Azima; Abd Kadir, Nur Farah Syahirah; Syed Mohamad, Sharifah Aminah; Ahmad, Nor Monica; Tan, Eddie Ti Tjih (2021)
Eggshell membrane (ESM) has a variety of nutrients including fibrous protein and glycosaminoglycans. The ESM can be separated and hydrolysed from Eggshell (ES) prior to further usage. However, there are not many reviews on the separation and hydrolysis methods of ESM so far. Hence, the present review compiles the ESM separation and hydrolysis studies reported to date. The literature search in this review was conducted by looking into a Web of Science (WoS) database. Most of the papers reported the use of manual peeling as a separation method followed by acid separation (hydrochloric acid and acetic acid) and mechanical separation (foam separator and stirred tank). The mechanically stirred tank is reported to be the most efficient separation method with the highest yield of ESM (80.2% to 90.9%). In addition, the ESM hydrolyses reported were predominantly done by using alcalase. The hydrolyses were done with various hydrolysis duration (1 – 12 hours) and temperatures (50oC – 55oC). In conclusion, most of the current separation of ESM prior to further usage was still focussing on manual hand peeling, while a large amount of the reported ESM hydrolysates was done by using alcalase.